2019
DOI: 10.1101/632273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting neurodevelopmental outcomes in children with perinatal HIV using a novel machine learning algorithm

Abstract: Background: A subset of children with perinatal HIV (pHIV) experience long-term neurocognitive symptoms despite treatment with antiretroviral therapy. However, predictors of neurocognitive outcomes remain elusive, particularly for children with pHIV residing in low-tomiddle income countries. The present study utilized a novel data analytic approach to identify clinically-relevant predictors of neurocognitive development in children with pHIV. Methods:Analyses were conducted on a large repository of longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Regarding specific metrics, a study utilizing a novel machine learning algorithm [ 13 ] aimed to identify clinically significant predictors of neurocognitive development in newborns with perinatal human immunodeficiency virus (HIV). Through multifactor regression with gradient boosting and fivefold cross-validation, the study successfully identified the predictors that have the greatest impact on the neurocognitive stability of newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding specific metrics, a study utilizing a novel machine learning algorithm [ 13 ] aimed to identify clinically significant predictors of neurocognitive development in newborns with perinatal human immunodeficiency virus (HIV). Through multifactor regression with gradient boosting and fivefold cross-validation, the study successfully identified the predictors that have the greatest impact on the neurocognitive stability of newborns.…”
Section: Introductionmentioning
confidence: 99%